FACTORS CONTRIBUTING TO THE IMPROVEMENT OF STRATEGIC MANAGEMENT IN NATIONAL CORPORATIONS - Badalova Zulfiya Kutbitdinovna,; Safarova Dilfuza Bakhramovna,; Karimova Diyora Alisher qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The article examines the factors for improving strategic management in national corporations and their impact on corporate development. The role of institutional environment, innovation, digital transformation, and human capital in enhancing strategic management efficiency is substantiated. Comprehensive strategic management approaches are proposed to strengthen competitiveness and ensure sustainable development of national corporations.